Wages, unemployment and inequality with heterogeneous firms and workers - Helpman, Elhanan 1946-; Itskhoki, Oleg 1983-; Redding, Stephen 1972- (NBER working paper series, 2008)
"In this paper we develop a multi-sector general equilibrium model of firm heterogeneity, worker heterogeneity and labor market frictions. We characterize the distributions of employment, unemployment, wages and income within and between sectors as a function of structural parameters. We find that greater firm heterogeneity increases unemployment, wage inequality and income inequality, whereas greater worker heterogeneity has ambiguous effects. We also find that labor market frictions have non-monotonic effects on aggregate unemployment and inequality through within- and between-sector components. Finally, high-ability workers have the lowest unemployment rates but the greatest wage inequality, and income inequality is lowest for intermediate ability. Although these results are interesting in their own right, the main contribution of the paper is in providing a framework for analyzing these types of issues"--National Bureau of Economic Research web site